ANALISIS SEKTOR UNGGULAN PROVINSI BANTEN DENGAN METODE LOCATION QUOTIENT DAN SHIFT SHARE - Sutanti Sutanti; Azizatul Munawaroh; Luqman Hakim (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze the leading sectors that have competitive competitiveness and specialization in Banten Province and determine the base sector’s priority as information and consideration, especially for the Banten Provincial Government in developing the economic development of Banten Province in the future. In addition to projecting the value of the Gross Regional Domestic Product of Banten Province in 2020. The data used in the form of sectoral Gross Regional Domestic Product of Banten Province and Indonesia's sectoral Gross Domestic Product based on constant prices in 2010 in the form of time series from 2010 to 2019 obtained from the Central Statistics Agency of Banten Province and the Central Statistics Agency of Indonesia. The data was then analyzed with a quantitative descriptive approach using the Location Quotient (LQ) model and Shift-Share analysis. Based on the LQ and Shift Share methods, there are 2 leading sectors in Banten Province, namely the Water Supply, Waste Management, Waste and Recycling sector, and the construction sector. Both sectors have an LQ above 1, which means that the sector is a base sector. In addition, the sector has positive Proportional Shift and Differential Shift which means the sector is growing fast and has a locational advantage. However, of the two sectors, when viewed nationally, the most superior share is in the construction sector because it has the highest national share value.